2018
DOI: 10.1080/14999013.2017.1416004
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric and Other Contributing Factors in Homicide-Suicide Cases, from Northern Gauteng, South Africa Over a Six-Year Period

Abstract: Homicide committed by a person who subsequently commits suicide within one week of the homicide, is a relatively rare event. The current study used an explanatory sequential design, including psychological autopsies, to identify psychiatric and other contributing factors in 35 homicide-suicide cases in northern Gauteng Province, South Africa. This research highlighted the complex multifactorial nature of these events. Identification of high-risk individuals and delineation of contributing factors is important.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(36 citation statements)
references
References 37 publications
0
35
1
Order By: Relevance
“…Most victims were female and the perpetrator's younger intimate partner (mean age 26.0 years). 15 It has been reported before that full-time employment is not protective against HS. 5 The most frequent findings with regard to the employment status of the perpetrator in the recent study were unemployment and employment in the security sector that requires carrying of a firearm (e.g.…”
Section: Characteristics Of Perpetrators and Victimsmentioning
confidence: 92%
See 4 more Smart Citations
“…Most victims were female and the perpetrator's younger intimate partner (mean age 26.0 years). 15 It has been reported before that full-time employment is not protective against HS. 5 The most frequent findings with regard to the employment status of the perpetrator in the recent study were unemployment and employment in the security sector that requires carrying of a firearm (e.g.…”
Section: Characteristics Of Perpetrators and Victimsmentioning
confidence: 92%
“…The HS classifications found in this study were 22 cases of intimate-possessive HS, 7 cases of filicidesuicide, 4 cases of familicide-suicide, 1 case of extrafamilial HS, and 1 case of familial-psychotic HS. 15 A review done in 2007 included 21 studies and 16 of these studies reported that more than 90% of perpetrators are male with a mean age of 40-50 years. In almost all HS between intimate partners the victims were female.…”
Section: Characteristics Of Perpetrators and Victimsmentioning
confidence: 99%
See 3 more Smart Citations